The Transformation and Leachability of Fly Ash/Cement Waste Forms Subjected to the Simultaneous Effect of Heat and Chemistry - Zhao Zheng; Hua Wen; Yuxiang Li; Min Qin; Yao Wang (Advances in Materials Science and Engineering)
The utilization of cement waste forms with high content of fly ash is a potential method in large-volume immobilization of low- and intermedium-level radioactive waste at near-surface. However, the migration behavior of radionuclides in fly ash/cement waste forms under geological environment is still unclear. This study researched the transformation of products, pore structure as well as the leachability of Ca2+, Na+, and simulated radioactive nuclides (Sr2+ and Cs+) in fly ash/cement waste forms under simultaneous effect through X-ray diffractometer (XRD), mercury intrusion porosimetry (MIP), and inductively coupled plasma optical emission spectroscopy (ICP-OES). Furthermore, the relationship between the decalcification and the leaching of Sr2+ and Cs+ was established by the fitting curves of apparent diffusion coefficient. The results indicated that the products of fly ash/cement waste forms were kept stable under simultaneous effect and the pore structure has excellent resistance to temperature. The increasing salt concentrations of leachant and temperature promoted the leaching of radionuclides while the protection layer formed at 60–80°C inhibited this phenomenon. The relationship of apparent diffusion coefficient between Sr2+ and Ca2+ was quadratic nonlinear, while the relationship between Cs+ and Ca2+ showed a linear relationship. Compared to cement waste forms, fly ash/cement waste forms were more stable. In addition, the long-term retention ability of fly ash/cement waste forms to Cs+ was more outstanding than Sr2+.